Experimental Investigations of Special Vehicles Vibration with Regard to Their Influence on Human Organism - Nader, M. (Engineering Transactions, 2000)
The paper presents investigations into the impact of vibration on drivers in selected vehicles Tatra 815 and Liaz. The investigations were carried out using the method of overall evaluation for constant rate of travel. It was found that the permissible limits of noxiousness, defined by the health protection regulations, were exceeded.